Projections from the paralemniscal nucleus to the spinal cord in the mouse - Liang, H.; Duan, D.; Watson, Charles; Paxinos, G. (Springer, 2013)
The present study investigated the projection from the paralemniscal nucleus (PL) to the spinal cord in the mouse by injecting the retrograde tracer fluoro-gold to different levels of the spinal cord and injecting the anterograde tracer biotinylated dextran amine into PL. We found that PL projects to the entire spinal cord with obvious contralateral predominance—420 neurons projected to the contralateral cervical cord and 270 to the contralateral lumbar cord. Fibers from PL descended in the dorsolateral funiculus on the contralateral side and terminated in laminae 5, 6, 7, and to a lesser extent in the dorsal and ventral horns. A smaller number of fibers also descended in the ventral funiculus on the ipsilateral side and terminated in laminae 7, 8 and, to a lesser extent in lamina 9. The present study is the first demonstration of the PL fiber termination in the spinal cord in mammals. The PL projection to the spinal cord may be involved in vocalization and locomotion.